Notch-1 Immunopositivity in Brain Lesions Associated with Pharmacoresistant Epilepsy - Dimitar Metodiev; Petia Dimova; Margarita Ruseva; Dimitar Parvanov; Rumiana Ganeva; Georgi Stamenov; Sevdalin Nachev; Vesela Ivanova; Rumen Marinov; Krassimir Minkin (Neuroglia)
Background: The Notch signaling pathway is an important regulator of stem cell activity in various tissues, including the central nervous system. It has been implicated in neurodevelopmental processes, including neuronal differentiation and synaptic plasticity. Research suggests that its expression may be associated with certain epileptogenic lesions, particularly those with neurodevelopmental origin. The aim of this study was to investigate the expression of Notch-1 in brain biopsies from various cases of pharmacoresistant epilepsy. Methods: Here, we used immunohistochemistry staining to retrospectively analyze 128 developmental lesions associated with pharmacoresistant epilepsy, including 13 cases with focal cortical dysplasia (FCD) type I, 39 with FCD type II, 37 with hippocampal sclerosis (HS), 23 with FCD IIIc, 9 with mild malformations of cortical development (MCD), 4 cases with mild malformation of cortical development with oligodendroglial hyperplasia and epilepsy (MOGHE), and 3 with tuberous sclerosis (TS). The tissues were stained for Neurofilament protein, Vimentin, S-100 protein, NeuN, and GFAP, as well as the stem cell marker Notch-1. Tissue that stained positively for Notch-1 was further characterized. Results: A positive Notch-1 reaction was found in all cases of FCD type IIb and TS, where it appeared in balloon cells but not in dysmorphic neurons, and in a single case of meningioangiomatosis (FCD IIIc), where it stained spider-like cells. Notch-1-positive cells showed a stem-like, glio-neuronal precursor immunophenotype. No staining was observed in the remaining cases with FCD type I, type III, HS, mild MCD, and MOGHE. Conclusions: Notch-1 displays a distinct pattern of expression in some epileptogenic lesions, potentially highlighting a stem cell-like origin or neurodevelopmental abnormalities contributing to pharmacoresistant epilepsy; however, it is not a general marker of such lesions. Its differential expression may prove useful in distinguishing between different types of FCD or other cortical malformations, which could assist in both their diagnosis and potentially in the development of more targeted therapeutic approaches. Further studies with different stem cell markers are needed in this direction.